2007
DOI: 10.1007/s00246-006-0013-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Outcomes for Preschool Children and Families After Surgery for Complex Congenital Heart Disease

Abstract: The purpose of the current study was to assess the psychosocial outcomes of preschool-aged survivors (ages 3-6 years) of hypoplastic left heart syndrome (HLHS; n=13) and transposition of the great arteries (TGA; n=13). Parents completed the following measures: Pediatric Quality of Life Inventory, Impact on the Family Scale, Parenting Stress Index, Parent Behavior Checklist, and Child Behavior Checklist. Quality of life scores did not differ from those of healthy controls. Parents of children with HLHS reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
130
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(145 citation statements)
references
References 28 publications
8
130
3
1
Order By: Relevance
“…However, there are only a few studies which have been carried out in pediatric populations using a generic HRQoL instrument or a cardiac disease-specific instrument [5,[8][9][10][11]. Recent results demonstrate that approximately 20% of children with cardiovascular disease report significantly impaired psychosocial quality of life irrespective of the severity of the disease [11].…”
Section: Introductionmentioning
confidence: 96%
“…However, there are only a few studies which have been carried out in pediatric populations using a generic HRQoL instrument or a cardiac disease-specific instrument [5,[8][9][10][11]. Recent results demonstrate that approximately 20% of children with cardiovascular disease report significantly impaired psychosocial quality of life irrespective of the severity of the disease [11].…”
Section: Introductionmentioning
confidence: 96%
“…Alterations in parental roles, the stress associated with decision making, and concerns regarding parental competence are all aspects that can contribute to parental psychological distress (Brosig, Mussatto et al, 2007;Hoehn et al, 2004;Lan et al;Pelchat et al, 1999). It is important to provide interventions for parents to reduce the psychological distress they endure (Miles et al, 1989) so that they are able to enjoy their child and emphasize the child's normal attributes (Drotar, Baskiewicz, Irvin, Kennell, & Klaus, 1975).…”
Section: Introductionmentioning
confidence: 97%
“…Considerable progress has been made within the last two decades in both the treatment and survival of infants with CHD (Brosig, Mussatto, Kuhn, & Tweddell, 2007;Gardner, Freeman, Black, & Angelini, 1996;Svavarsdottir & McCubbin, 1996;Torowicz, Irving, Hanlon, Sumpter, & Medoff-Cooper, 2010). Parents of children born with CHD are likely to experience a variety of stressors and psychological distress associated with their child's illness.…”
Section: Introductionmentioning
confidence: 99%
“…(6)(7)(8)(9) Research findings on parenting stress outcomes in children with CHD are conflicting, with some investigators reporting that parents experienced higher levels of stress, (1,6,7,10,11) whilst others have found stress levels to be similar to those experienced by parents of healthy children; in fact, in some instances parents of children with CHD have even reported lower stress levels than parents of healthy children. It has been suggested that these parents have likely developed a higher threshold for what they perceive to be stressful due to their experiences with their child with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these parents have likely developed a higher threshold for what they perceive to be stressful due to their experiences with their child with CHD. (8,9,11) Research findings suggest considerable variability in individual stress outcomes with disease severity, the changing health status of the child, specific stressors in play at the time and resiliency factors all, in part, explaining the variability. (2,12) In addition, the extent of the burden of care, social isolation and financial difficulties have also been shown to heighten the risk of long-standing psychosocial problems.…”
Section: Introductionmentioning
confidence: 99%